Von Kunst leben : Selbstmarketing für bildende Künstler*innen - Jacobi, Andrea (transcript Verlag, 2023)
This note is part of Quality testing.
Keywords: Art -- Marketing.; Art -- Vocational guidance.; Art -- Commercialisation.; Art -- Orientation professionnelle.; art market.; BUSINESS & ECONOMICS / Management.